Peran Pendapatan Asli Daerah (PAD) Terhadap Anggaran Pendapatan dan Belanja Daerah (APBD) Dalam Mendukung Pelaksanaan Otonomi Daerah di Kabupaten Bima. - Sahrudin; Abdul Azim Wahbi; Muhammad Buhais (CV. Eureka Murakabi Abadi, 2026)
This study aims to analyze the role of Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) in the Regional Revenue and Expenditure Budget (Anggaran Pendapatan dan Belanja Daerah/APBD) in supporting the implementation of regional autonomy in Bima Regency. The study employs a quantitative descriptive approach and analyzes secondary data covering the period from 2020 to 2025 to identify the contribution of PAD in supporting regional autonomy. The findings indicate that the contribution ratio of PAD to transfer funds reflects a low level of fiscal independence in Bima Regency, with an average ratio of 9.47% (categorized within the 0–25% range), indicating a high dependency on central government transfers. The effectiveness ratio of PAD is categorized as moderately effective, with an average of 87.48%, suggesting that PAD realization generally meets or exceeds the established targets. Furthermore, the growth ratio of PAD shows a fluctuating trend but remains within an ideal category, with an average growth rate of 25.27% per year, exceeding the minimum growth threshold recommended in regional financial management regulations. These results highlight the importance of optimizing local economic potential in the implementation of regional autonomy. Therefore, strengthening fiscal independence through sustainable PAD enhancement is a key factor in achieving effective and sustainable regional autonomy.